2019
DOI: 10.1186/s13075-019-1963-2
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib facilitates the expansion of myeloid-derived suppressor cells and ameliorates interstitial lung disease in SKG mice

Abstract: Background Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) is a sometimes life-threatening complication in RA patients. SKG mice develop not only arthritis but also an ILD resembling RA-ILD. We previously reported that tofacitinib, a JAK inhibitor, facilitates the expansion of myeloid-derived suppressor cells (MDSCs) and ameliorates arthritis in SKG mice. The aim of this study was to elucidate the effect of tofacitinib on the ILD in SKG mice. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 22 publications
2
49
0
1
Order By: Relevance
“…Using a classical gating strategy (Ly6G -CD11b + Ly6C high SSC low ) for mMDSCs (99), mMDSCs were identified with FACS and found to be decreased in combination (CIA+ODE) exposure group. These findings are consistent with a recent report that showed that the expansion of MDSCs following tofacitinib treatment is inversely related to the progression of ILD in the SKG mouse model of RA-ILD (116). These collective findings would suggest a potential protective role for lung MDSCs (particularly mMDSCs) in the development RA-related lung disease, and future studies are warranted to understand their role in disease manifestations to potentially develop novel targets for therapeutic interventions.…”
Section: Discussionsupporting
confidence: 91%
“…Using a classical gating strategy (Ly6G -CD11b + Ly6C high SSC low ) for mMDSCs (99), mMDSCs were identified with FACS and found to be decreased in combination (CIA+ODE) exposure group. These findings are consistent with a recent report that showed that the expansion of MDSCs following tofacitinib treatment is inversely related to the progression of ILD in the SKG mouse model of RA-ILD (116). These collective findings would suggest a potential protective role for lung MDSCs (particularly mMDSCs) in the development RA-related lung disease, and future studies are warranted to understand their role in disease manifestations to potentially develop novel targets for therapeutic interventions.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, tofacitinib demonstrated its ability to facilitate the expansion of myeloid-derived suppressor cells (MDSC) and ameliorate arthritis in SKG mice, a murine model developing not only arthritis but also ILD. In SKG mice, tofacitinib significantly suppressed the progression of ILD compared to control, by increasing myeloid-derived suppressor cells and suppressing Th17 cells proliferation and differentiation [180]. On the contrary, in another in vitro study, the JAK2 inhibition, but not the selective JAK1/JAK3 pathway, significantly reduced IL-17A-induced fibrogenic response in RA-ILD patients [181].…”
Section: Targeted Synthetic Disease-modifying Antirheumatic Drugs (Tsmentioning
confidence: 94%
“…Injection of zymosan into SKG mice can induce RA-ILD (Redente et al, 2018;Sendo et al, 2019). SKG female mice were injected with zymosan to construct RA-ILD mouse models.…”
Section: High Expression Of Hdac3 and Il17ra In Lung Tissues Of Ra-ilmentioning
confidence: 99%